Local scour at single piers revisited - Fael, Cristina (2014)
The paper summarizes recent contributions of the authors on the effects of relative flow depth,relative sand size, time and fluid viscosity, on the scour depth at single piers. These contributions rely on unique experiments in the sense that they are systematically longer than the vast majority of those found in the literature. The characterization of the effects of relative sand size and time is further improved as compared with existing literature while the effect of the relative flow depth confirms previous findings. New predictors are suggested. Viscous effects conveyed by the approach flow seem non-negligible; this is a new contribution that deserves further research.